Improving Social Interaction among Primary School Students with Stuttering - Walaa H. Romieh; Hend I. Imbaby; Salwa Al Majali (Islamic Guidance and Counseling Journal, 2023)
The research aimed to examine the effectiveness of a guidance program in enhancing social interaction abilities among elementary school students with stuttering. The sample consisted of 20 students, divided into two groups. Prior to the intervention, both groups were assessed using a social interaction scale. Subsequently, the experimental group underwent the 17-sessions guidance program, which aimed at developing social interaction skills. On the other hand, the control group did not receive any intervention. Following the intervention, the same social interaction scale was administered to both groups. The results indicated statistically significant differences between the levels of social interaction in the experimental group and the control group, favoring the experimental group. Additionally, there were no statistically significant differences between the average ranks of the two measurements (post-follow-up) concerning social interaction among elementary school students who stutter in the experimental group.